KAJIAN GEOMORFOLOGI KOMPLEKS GUA SEPLAWAN KAWASAN KARST JONGGRANGAN - Arif Ashari (Geo Media: Majalah Ilmiah dan Informasi Kegeografian, 2013)
This research aims to study the geomorphology of Seplawan cave in Karst region Jonggrangan. This includes : (1) the type of cave and landform around the cave, (2) the type of cave tunnel, and (3) the existence of speleothem and speleogen in the cave. The geomorphologic study of caves provides useful information to demonstrate a track record of karst development as well as to guide the development of cave tourism. The method employed in this research is a geomorphologic survey by focusing on morphology and morfogenesa. The data was collected through observation, documentation, and literary study. The data analysis was performed using descriptive-morphologic and spatial analysis. The findings show that seplawan cave belongs to the category of pit cave, formed by the widening of the ponor hole in the doline base. The tunnel in the cave have different forms namely, passage eliptical, rectangular passage, canyon, and joint passage. Speleothem in the form of stalactites, stalagmites, and drappery is found near the mouth of the cave. Moreover, the speleogen in the form of a notch solution, solution pocket, pothole, scallops, and Karren anastomoses is found in all parts of the cave.Keywords: karst geomorphology, karst caves, speleothem, speleogen